Geotechnical Engineering Properties of Soils Solidified by Microbially Induced CaCO3 Precipitation (MICP) - Jia Liu; Gang Li; Xi’an Li (Advances in Civil Engineering)
Microbially induced calcium carbonate precipitation (MICP) uses the metabolic function of microbes to carry out biochemical reactions with other substances in the environment. Through the controlled growth of inorganic minerals, soil particles are cemented and soil pores are filled to solidify the soil and reduce its permeability. Thus, the application of this technology was foreseen in geotechnical engineering and environment (building antiseepage, contaminated soil restoration, slope soil erosion, and sand liquefaction). In this review article, based on current research findings, the urea hydrolysis and the cementation mechanism of MICP are briefly described. The influences of factors such as enzyme activity, cementation solution concentration, pH, temperature, grouting method, and particle size on MICP-treated soil are discussed. The engineering properties of MICP-treated soils are evaluated, for instance, the strength, stiffness, liquefaction resistance, permeability, and durability. The applications of MICP technology in ground improvement, geotechnical seepage control, foundation erosion resistance, and fixation of heavy metals are summarized. Finally, future directions of the development of MICP technology are elucidated to provide a reference and guidance for the promotion of MICP technology in the geotechnical engineering field.